Event Structure vs. Stage Structure and Abstract Aspectual Relations - Patrick Caudal; Roussarie, Laurent (Proceedings of the Twenty-Sixth Annual Meeting of the Berkeley Linguistics Society: General Session and Parasession on Aspect (2000), 2000)
Introduction v Currently dominant neo-davidsonian view on aspect calculus has driven many to study event structure in terms of mereological, part-of relationships ; it will be argued here that this approach is not appropriate for theoretical & empirical reasons (cf. Asher (1993) & Verkuyl (1993) for related positions, on philosophical grounds); v An alternative approach based on discourse-like relations will be proposed. Main features : Explicit relations between situations, sub-situations (or situation stages) and aspectual viewpoints ; Empirical evidence in a variety of languages suggesting indeed that event types / event structure (= situation structure / eventuality structure) should be regarded as a language-specific issue. 2 Preliminary definitions : some basic aspectual concepts 2.1 Defining situation structure and lexical aspect